Sosialisasi dan Diskusi Persiapan Akreditasi Program Studi D4 Manajemen Informatika Politeknik Negeri Sriwijaya Tahun 2023 - Alem Pameli; Trizaurah Armiani; Muhammad Aris Ganiardi; Indri Ariyanti; Yulia Hapsari; Rika Sadariawati; M Arief Rahman (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
In the midst of the digital revolution, the role of higher education has assumed a heightened significance in a nation's overall development. The accreditation of study programs within higher education institutions holds paramount importance in assuring the quality of tertiary education. This article underscores the significance of accrediting the Informatics Management Study Program at Sriwijaya State Polytechnic (Polsri) as a means to enhance the quality of higher education. By means of socialization and discussions, the various stakeholders associated with the Informatics Management Study Program acquire a profound comprehension of the accreditation process and the requisite standards to be met. The outcomes of this research substantiate that these steps not only foster an improved understanding but also promote collaboration among the stakeholders. Consequently, they are better prepared to confront external evaluations with heightened preparedness and self-assurance.